KAJIAN PENGEMASAN TERHADAP MUTU TERUNG UNGU (Solanum melongena L) SELAMA PENYIMPANAN - Victoria Vallen Paath; Frans Wenur; Ireine Longdong (Universitas Sam Ratulangi, 2017)
ABSTRACTThe purpose of this study was to determine the proper type of packaging and storage temperature in extending the self life of the purple eggplant, to determine the model of eggplant weight change during storage and to determine the physical changes and storage life of eggplant. The research method used is experimental method with descriptive analysis with two packaging treatment HDPE, stretch film and one control. The lowest decrease of weight percentage was on eggplant with HDPE packing at 8.85 Í¦C storage temperature of 1.30%, with the hardness value of 0.12 mm/ g, on the base, center of eggplant 0.14 mm / g and on the tip was 0,13 mm/g. After 44 days storage, the hardness of the base of the eggplant was 0.09 mm / g, the center of the eggplant was 0,09 mm / g, and the end of eggplant was 0,12 mm / G. The eggplant changed color by browning at the base and began to rot on the 38th day until the 44th day, and the best weight change model at HDPE 8.85 Í¦C. with the equation model of line y = 0,1094x - 0,2617And the correlation coefficient of R2 = 0.8265.Keywords : Purple eggplant, quality, packaging.